Upaya Peningkatan Kualitas Dengan Metode PDCA Di PT Astra Komponen Indonesia - Yonatan, Jong Feliando; Palit, Herry Christian (Jurnal Titra, 2015)
The quality is an important thing that should be mentioned because related to the customer satisfaction. PT ASKI challenge an enourmous on painting quality. The average of rejection from the painting process output reached 21,29% in 2014. An improvement of quality should be done to increase the product quality. To solve the quality problem, 8 steps of PDCA (plan-do-check-action) were chosen. The result of improvement activities were not always giving a positive result, but still working as the guidence to do the next improvement activity.